Diversity and Abundance of Dragonfly (Anisoptera) and Damselfly (Zygoptera) at Sabo Dam Complang, Kediri, East Java, Indonesia - Susanto, Muhamad Azmi Dwi; Arianti, Okta Fina (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This research aimed to identify and analyze the diversity and abundance of dragonflies and damselflies species at Sabo Dam Complang. The samples were taken using the VES (Visual Encounter Survey) method and two transect methods: line transects, and belt transects. The data obtained were analyzed using the Shannon-Wienner species diversity index (H') and the relative abundance of species (RA). The results showed that at Sabo Dam Complang, the researchers found 11 species with a total of 63 individuals dragonfly of Anisoptera suborder and nine species with a total of 160 individuals from 5 families in the Zygoptera suborder. The results of this research show a diversity index value of 2.59.